Studi Dampak Sabun Ramah Lingkungan Terhadap Kualitas Tanah Ditinjau dengan Indikator Cacing Tanah (Lumbricus terrestris) - Firda Arriva Alyssa Ghufron (Jurnal Pendidikan Biologi Undiksha, 2023)
Soap as a cleaning agent is a class of products formulated with chemicals designed to meet consumer needs. However, household waste derived from chemicals affects how water and soil quality in the area. This study was conducted to determine the impact of environmentally friendly soap on soil quality in terms of earthworm indicators (Lumbricus terrestris). The methods used in this research are experimental and observational research methods. The main instrument in this research is using earthworms as bioindicators to measure soil quality. The rose purslane plant as a control variable in the study is a supplying agent of oxygen in the experimental media. The independent variables consisted of 4 different types of environmentally friendly soap brands. The dependent criteria observed to measure soil quality are the survival of earthworms and control plants, the number of worms that survive and soil surface characteristics. Data analysis was conducted using a descriptive qualitative approach. Results will be presented in the form of phenomenon analysis based on experimental data. The results show that natural soap is proven to be safe for the soil which is unlikely to cause pollution as indicated by the number of earthworms that are able to survive. This is concluded from the analysis of the average media that is able to make earthworms survive and be able to grow.